AB098. Defocused low-energy shock wave can stimulate penile tissues to produce more energy for growth and proliferation in a DMED rat model - Bae, Woong Jin (Transl Androl Urol, 2017)
BACKGROUND: Defocused low-energy shock wave therapy (DL-ESWT) is a novel and potential way in regeneration medicine, and now it has been used in many areas which have demonstrated its unique superiority. At present, some researchers have applied ESWT to clinical therapy for erectile dysfunction (ED), which achieves satisfactory therapeutic effects. However, the metabolic change of corpus cavernosum with ESWT is still unclear. To investigate the metabolic change of corpus cavernosum with ESWT in a rat model of DMED induced by streptozotocin (STZ). METHODS: We divided human umbilical vein endothelial cells (HUVECs) in three groups. Group 1 is control group, without ESWT. Group 2 is half treated group, with ESWT for former three passages. Group 3 is full treated group, and we applied ESWT to HUVECs for every passage. After five passages, we collected the cells, supernatants and proteins for ELISA and Western blot. The DMED rats were randomly divided into 2 groups (N=10 per group): 1 DMED group, 2 DMED + ESWT group. The normal group (N=10, without STZ) is the control group. Erectile function and other expression experiments were carried out after STZ injection of 8 weeks. ESWT was repeated 3 times per week with one day’s break, for a total duration of 4 weeks. Immediately after recording of intracavernous pressure (ICP), the penis was then harvested for histologic analysis, ELISA and western blotting. RESULTS: The ratio of ICP/MAP was significantly higher in the ESWT group than in the DMED groups (P<0.05). Expression of growth factors increases after ESWT in vitro (P<0.05). ESWT can promote proliferation of endothelial cells in corpus cavernosum. The result was significantly higher in the ESWT group than in the DMED group (P<0.05). ESWT can improve cell metabolism in vivo. The expression of mitochondrial membrane proteins is higher in the ESWT group than in the DMED group (P<0.05). And the lactate concentration is higher in the ESWT group than in the DMED group (P<0.05). CONCLUSIONS: There was a metabolic coupling between oxidative phosphorylation and anaerobic glycolysis of cells in the corpus cavernosum. And after ESWT there were a lot of lactic acid produced by anaerobic glycolysis of endothelial cells taking part in the tricarboxylic acid cycle of cells in corpus cavernosum, which could generate a great deal of energy to support growth and proliferation.